Effects of Interleukin-1β in Glycinergic Transmission at the Central Amygdala - Solorza, Jocelyn; Oliva, Carolina A.; Castillo, Karen; Amestica, Gabriela; Maldifassi, María Constanza; López-Cortés, Xaviera A.; Barra, Rafael; Stehberg, Jimmy; Piesche, Matthias; Sáez-Briones, Patricio; González, Wendy; Arenas-Salinas, Mauricio; et al. (Frontiers in Pharmacology, 2021)
Interleukin-1β (IL-1β) is an important cytokine that modulates peripheral and central pain sensitization at the spinal level. Among its effects, it increases spinal cord excitability by reducing inhibitory Glycinergic and GABAergic neurotransmission. In the brain, IL-1β is released by glial cells in regions associated with pain processing during neuropathic pain. It also has important roles in neuroinflammation and in regulating NMDA receptor activity required for learning and memory. The modulation of glycine-mediated inhibitory activity via IL-1β may play a critical role in the perception of different levels of pain. The central nucleus of the amygdala (CeA) participates in receiving and processing pain information. Interestingly, this nucleus is enriched in the regulatory auxiliary glycine receptor (GlyR) β subunit (βGlyR); however, no studies have evaluated the effect of IL-1β on glycinergic neurotransmission in the brain. Hence, we hypothesized that IL-1β may modulate GlyR-mediated inhibitory activity via interactions with the βGlyR subunit. Our results show that the application of IL-1β (10 ng/ml) to CeA brain slices has a biphasic effect; transiently increases and then reduces sIPSC amplitude of CeA glycinergic currents. Additionally, we performed molecular docking, site-directed mutagenesis, and whole-cell voltage-clamp electrophysiological experiments in HEK cells transfected with GlyRs containing different GlyR subunits. These data indicate that IL-1β modulates GlyR activity by establishing hydrogen bonds with at least one key amino acid residue located in the back of the loop C at the ECD domain of the βGlyR subunit. The present results suggest that IL-1β in the CeA controls glycinergic neurotransmission, possibly via interactions with the βGlyR subunit. This effect could be relevant for understanding how IL-1β released by glia modulates central processing of pain, learning and memory, and is involved in neuroinflammation.